The Impacts of Agricultural Development Project on Women: a Case Study of the Eastern Islands Smallholder Farming Systems and Livestock Development Project (EISFSLDP) - Fawzia Sulaiman (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1998)
EnglishThe Eastern Islands Smallholder Farming Systems and Livestock Development Project (EISFSLDP) is a poverty alleviation project targeted for increasing income of a selected number of relatively poor rural households. The EISFSLDP project is carried out through an agribusiness approach to farming system development in three provinces in eastern part of Indonesia (South Sulawesi, North Sulawesi, and Maluku Provinces). Even though the problem of mainstreaming women in a development project has been anticipated in the project design and the project management has conducted some efforts to increase the involvement and participation of women in the project, but the problem still persists. The cultural values and norms of project staff and communities in the project areas have resulted a perception that the project beneficiaries are heads of households who are usually males.Although there was a significant difference of time allocation in carrying out reproductive activities between women from project participant households and women from non project participant households, which was due to the time allocated to look for forage (among women from project participant households), but they perceived that there was no negative impact of the project on their time allocation in carrying out reproductive and productive activities, attending community activities, and on their leisure time. Due to the very limited opportunity for income generating activities, and their relatively adequate leisure time (ranging from 9.4 hours-11 hours per day), they perceived that their involvement in managing project packets was beneficial in using their time for productive activities.Even though the majority of women from project participant households were involved actively in managing project packets (ranging from 62 to 95%) and they contributed significantly in farming activities, but they were. not invited to attend farmer training and farmer group meeting. Despite the disadvantageous socio-cultural values in the project locations, the initial efforts of the project management to mainstream women into all aspects of project implementation should be consistently integrated into the project policy, project planning and program development, project technical guidelines, project administration such as in gender segregated reporting system, and project monitoring and evaluation. In this respect, gender analysis should be conducted in all project sites as a tool for an accurate basis for decision makings in the effort to increase the involvement and contribution of all members of project participant households, including women.IndonesianProyek Pengembangan Usaha Tani dan Ternak di Kawasan Timur Indonesia (the Eastern Islands Smallholder Farming Systems and Livestock Development Project) adalah suatu proyek penanggulangan kemiskinan yang bertujuan untuk meningkatkan pendapatan petani yang relatif miskin, melalui pendekatan agribisnis dengan pengembangan sistem usaha tani, di tiga propinsi Kawasan Timur Indonesia (Sulawesi Selatan, Sulawesi Utara, dan Maluku). Walaupun masalah penyertaan wanita telah diantisipasi di dalam desain proyek, dan manajemen proyek telah melakukan beberapa upaya untuk meningkatkan partisipasi dan penyertaan wanita dalam proyek, tetapi ternyata pengintegrasian penyertaan wanita kedalam implementasi proyek masih mengalami kendala. Norma dan nilai budaya dari staf proyek dan masyarakat di lokasi proyek merupakan salah satu penyebab dari anggapan bahwa peserta proyek adalah kepala keluarga yang biasanya laki-laki.Walaupun alokasi waktu untuk melakukan kegiatan reproduksi pada wanita dari keluarga peserta proyek berbeda nyata dengan wanita dari nonpeserta proyek yang terutama karena diperlukannya alokasi waktu untuk melakukan kegiatan pencarian pakan hijauan ternak (pada wanita dari keluarga peserta proyek), tetapi mereka beranggapan bahwa tidak ada dampak negatif dari keterlibatannya dalam pengelolaan paket proyek terhadap alokasi waktu untuk kegiatan produksi dan produksi, hadir dalam pertemuan kemasyarakatan, dan terhadap waktu luang dan beristirahat. Sangat terbatasnya kesempatan untuk kegiatan yang menghasilkan pendapatan di desa, dan adanya waktu luang dan istirahat yang relatif cukup (berkisar antara 9,4 -11 jam per hari), justru menyebabkan keterlibatan wanita dalam pengelolaan proyek dianggap sebagai bermanfaat dalam penggunaan waktu untuk kegiatan yang produktif.Walaupun sebagian besar wanita dari rumah tangga peserta proyek terlibat dalam pengelolaan paket proyek (berkisar antara 62- 95%), dan kontribusinya cukup besar dalam kegiatan usaha tani, tetapi mereka tidak dilibatkan dalam pertemuan kelompok tani proyek dan dalam kursus tani. Oleh karena itu, upaya-upaya awal yang telah dilakukan manajemen proyek dalam meningkatkan partisipsi dan keterlibatan wanita dalam semua aspek pengimplementasian proyek perlu secara konsisten diintegrasikan ke dalam kebijaksanaan proyek, penyusunan program dan perencanaan proyek, petunjuk teknis kegiatan, administrasi proyek seperti sistem pelaporan dengan segregasi jender, serta monitoring dan evaluasi. Dalam hal ini, perlu dilakukan analisis jender di semua lokasi proyek sebagai dasar pengambilan keputusan yang akurat dalam upaya meningkatkan penyertaan dan keterlibatan semua anggota keluarga dalam pengelolaan paket proyek, termasuk anggota keluarga wanita.